Learning lexical tone through statistical learning in non-tone language speakers - Tang, Mi; Spenader, Jennifer; Jones, Stephen (Frontiers in Education, 2024)
This study investigates the role of statistical learning in the learning of lexical tones by nontone language speakers. Over two experiments, participants were exposed to tone-syllable combinations with conditioned patterns. Experiment 1 used a typical statistical learning paradigm without feedback to assess participants' ability to discriminate tone-syllable combinations. The results revealed significant syllable learning but not tone learning. Experiment 2 controlled for syllable occurrence to isolate the learning of tonal patterns and demonstrated above-chance learning accuracy from the first training day, indicating successful lexical tone learning through the statistical learning mechanisms. The findings suggest that statistical learning without feedback facilitates lexical tone learning. Our study not only supports the universality of statistical learning in language acquisition but also prompts further research into its application in educational settings for teaching tonal languages.